2016
DOI: 10.1105/tpc.15.01001
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop Governed by SUB1A1 Interaction with MITOGEN-ACTIVATED PROTEIN KINASE3 Imparts Submergence Tolerance in Rice

Abstract: ORCID IDs: 0000-0003-3694-6378 (P.S.); 0000-0003-0820-9936 (A.K.S.)Mitogen-activated protein kinase (MAPK) signal transduction networks have been extensively explored in plants; however, the connection between MAPK signaling cascades and submergence tolerance is currently unknown. The ethylene response factor-like protein SUB1A orchestrates a plethora of responses during submergence stress tolerance in rice (Oryza sativa). In this study, we report that MPK3 is activated by submergence in a SUB1A-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 56 publications
4
77
0
Order By: Relevance
“…In parallel the leaves transformed with empty vector served as control. After infection of transformed leaves with X. oryzae , OsMPK7 protein was immunoprecipitated using anti-GFP antibody and immunoblotting was carried out with pTEpY antibody23. Increase in phosphorylation of OsMPK7 was observed in the samples infected with X. oryzae as compared to non-infected controls (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In parallel the leaves transformed with empty vector served as control. After infection of transformed leaves with X. oryzae , OsMPK7 protein was immunoprecipitated using anti-GFP antibody and immunoblotting was carried out with pTEpY antibody23. Increase in phosphorylation of OsMPK7 was observed in the samples infected with X. oryzae as compared to non-infected controls (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, a unique interaction was reported among two MAPKs in rice, OsMPK3 and OsMPK20-4 that showed resistance against P. syringae infection when transiently expressed in tobacco leaves22. Moreover, a recent study reports a unique role of rice MPK3 in imparting submergence tolerance regulated by SUB1A1 by a positive feedback loop23. However, involvement of rice MAPKs particularly of group C in pathogen signaling still remains elusive.…”
mentioning
confidence: 99%
“…So far, it is unclear which signals activate ERFVIIs upon low-oxygen stress in Arabidopsis. The non-N-end rule ERFVII target SUB1A of rice was shown to be a MPK phosphorylation target, (Singh and Sinha, 2016), suggesting posttranslational signal integration. Interestingly, MPK3/6 activity in Arabidopsis is induced by a mitochondrial signal upon oxygen deprivation (Chang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the tolerant allele SUB1A1 was shown to bind to the promoter of MPK3 and regulated its expression in a positive regulatory loop during submergence stress signaling. 5 The MAPK signaling cascade is a 3-tier phospho-relay signaling module that is evolutionarily conserved in all eukaryotes. 6,7 In plants, the MAPK signal transduction network is implicated in various biotic and abiotic stress responses, Recently, MAPK was also shown to act as a nodal point of crosstalk between SUB1A1 and submergence signaling pathways.…”
mentioning
confidence: 99%
“…4 It lacks the SUB1 locus, which is responsible for imparting submergence tolerance. Singh and Sinha 5 have recently demonstrated a phosphorylation-based regulation of SUB1A1 by an MPK3 module in Swarna Sub1. The study reported that MPK3 is activated by submergence in a SUB1A-dependent manner.…”
mentioning
confidence: 99%